2004
DOI: 10.1111/j.1349-7006.2004.tb03258.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of an anti‐angiogenic substance from Agaricus blazei Murill: Its antitumor and antimetastatic actions

Abstract: We previously found that ergosterol isolated from Agaricus blazei inhibited tumor growth through the inhibition of tumor-induced neovascularization. In the present study, we isolated further anti-angiogenic substances (A-1 and A-2) from this fungus using an assay system of angiogenesis induced by Matrigel supplemented with vascular endothelial growth factor, and A-1 was identified as sodium pyroglutamate. Next, we examined the antitumor and antimetastatic actions of A-1 using Lewis lung carcinoma ( he Basiodio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 17 publications
2
59
0
2
Order By: Relevance
“…In recent years, many studies have reported that different extracts of A. blazei Murill have various anticancer effects, ranging from the improvement of immune-modulatory activity (19)(20)(21) to the inhibition of tumor growth via direct inhibition of tumor-induced angiogenesis in mice (7). The results of the present study confirmed that fraction FA-2-b-ß did induce the apoptosis of HL-60 cells in vitro as indicated by morphological changes, DNA fragmentation and flow cytometry.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In recent years, many studies have reported that different extracts of A. blazei Murill have various anticancer effects, ranging from the improvement of immune-modulatory activity (19)(20)(21) to the inhibition of tumor growth via direct inhibition of tumor-induced angiogenesis in mice (7). The results of the present study confirmed that fraction FA-2-b-ß did induce the apoptosis of HL-60 cells in vitro as indicated by morphological changes, DNA fragmentation and flow cytometry.…”
Section: Discussionsupporting
confidence: 79%
“…Research has indicated that the primary medical effect of A. blazei Murill is its anticancer activity in tumor-bearing mice (12). A. blazei Murill has been reported to be very effective against some malignancies, and possible explanations of its anticancer action have been proposed (2,3,7,8). The details of the mechanism, however, are still unclear.…”
Section: Introductionmentioning
confidence: 97%
“…Agaricus blazei contains active organic compounds associated with the maintenance of human health and the healing of diseases. Pharmacological studies have shown that bioactive substances, such as polysaccharide-protein complexes (PSPC) from A. blazei, function as antioxidants, antimutagenics, antitumorigenics, and anticancer agents (Kimura et al, 2004;Firenzuoli et al, 2008). However, the harvesting time of A. blazei is relatively long (approximately 60 days) when compared to other related Agaricus sp., including A. bisporus (approximately 30 days) (Pardo-Gimenez et al, 2010;Chu et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…It has been quite recently shown that pyroglutamate contained in Agaricus blazei inhibited tumor growth by in vivo experiments on tumor-implanted mice. 14) These results suggest that Agaricus blazei has strong potential as an alternative medicine.…”
mentioning
confidence: 69%